Xenopus Resources: Transgenic, Inbred and Mutant Animals, Training Opportunities, and Web-Based Support - Horb, Marko; Wlizla, Marcin; Abu-Daya, Anita; McNamara, Sean; Gajdasik, Dominika; Igawa, Takeshi; Suzuki, Atsushi; Ogino, Hajime; Noble, Anna; , Centre de Ressource Biologique Xenope team in France; Robert, Jacques; James-Zorn, Christina; et al. (Frontiers in Physiology, 2019)
Two species of the clawed frog family, Xenopus laevis and Xenopus tropicalis, are widely used as tools to investigate both normal and disease-state biochemistry, genetics, cell biology and developmental biology. To support both specialist and non-specialist scientists needing access to these models for their research, a number of centralised resources exist around the world. These include centres that hold live and frozen stocks of transgenic, inbred and mutant animals and centres that hold molecular resources. This infrastructure is supported by a model organism database. Here we describe much of this infrastructure and encourage the community to make the best use of it and to guide the resource centres in developing new lines and libraries.